S-carboxymethylcysteine in the treatment of glue ear: quantitative systematic review - Moore, Robert Andrew (BioMed Central, 2001)
OBJECTIVE: To establish the clinical relevance of S-carboxymethylcysteine in the treatment of glue ear in children using measures approximating those saving a child from operation for grommet insertion. DATA SOURCES: Cochrane Library, MEDLINE, EMBASE, PubMed, reference lists and reviews were used for randomised controlled trials comparing S-carboxymethylcysteine with placebo. Seven trials involving 283 children and 146 ears were found. REVIEW METHODS: Studies were randomised, double-blind comparisons of S-carboxymethylcysteine (any dose and duration) with placebo in otitis media with effusion. Quality of trial reporting and validity of methods were assessed and used in sensitivity analysis. Main outcomes were relative benefit and number-needed-to-treat to prevent one grommet operation compared with placebo. RESULTS: Successful outcomes were obtained in 17% of children given placebo (range 5% to 38% in individual studies) and in 35% of children given S-carboxymethylcysteine (range 22 to 80%). For combined data (children and ears) the relative benefit was 2.0 (95%CI 1.4 to 2.8) and number-needed-to-treat 5.5 (95% confidence interval 3.8 to 9.8). Pooled data from trials of higher reporting quality (4/7) or methodological validity (3/7) tended to have lower efficacy but were not statistically different from those of lower quality or validity. CONCLUSION: S-carboxymethylcysteine is effective in the treatment of children with glue ear. For every five or six children treated with S-carboxymethylcysteine over one to three months, one will not undergo surgery for grommet insertion who would have done had they been given placebo. The confidence in this conclusion is limited because studies included relatively few children.